Green Banking Practices and Sustainable Banking in Pakistan: The Mediating Role of Intentions to Adopt Green Banking - Sadiq Ullah Khan,; Dr. Tufail Nawaz,; Muhammad Asadullah,; Maqsood Ur Rehman,; Ifrah Younas,; Dr. Khalid Rehman (Corresponding Author), (Al-Qanṭara, 2023)
The study examined the effect green banking practices on sustainable banking in Pakistan with mediating role of intentions to adopt green banking. Five green banking practices i.e. perceived usefulness, perceived ease of use, management commitment and support, competitors' pressure, and customer pressure were selected to test the proposed relationships. Respondents of the study included randomly selected 400 banking sector employees employed at commercial banks in Khyber Pakhtunkhwa province of Pakistan. Data were collected through a combined 37 items survey questionnaire. Data were analysed using structural equation modelling to examine the path and structural models. The results of the study revealed that all the selected green banking practices have significant effect on intentions to adopt green banking as well as sustainable banking except ease of use and sustainable banking. Further, intentions to adopt green banking mediated the relationship between green banking practices and sustainable banking in Pakistan.